Composition and distribution of zooplankton in the Laptev Sea and adjacent Nansen Basin during summer, 1993. - Kosobokova, Ksenia N; Hirche, Hans-Jürgen (PANGAEA, 2014)
This data collection contains surface temperature, salinity and ice coverage as well as zooplankton abundance measured on multinet samples during POLARSTERN cruise ARK-IX/4 to the Laptev Sea and Arctic Ocean in 1993.
Zooplankton abundance and physical oceanography during POLARSTERN cruise ARK-IX/4 to the Laptev Sea and Arctic Ocean in 1993